The father of Jewish mysticism : the writing of Gershom Scholem - Weidner, Daniel (New Jewish philosophy and thought., 2022)
"The Father of Jewish Mysticism offers an incisive look at the early life and writings of Gershom Scholem (1897-1982), the father of modern Jewish mysticism and a major 20th-century Jewish intellectual thinker. Daniel Weidner offers the first full-length study, published in English, of Scholem thought. Scholem, a historian of Kabbalah and sharp critic of Jewish assimilation, played a major role in the study and popularization of Jewish mysticism. Through his work on Kabbalah, Scholem turned the closed world of mystical texts into a force for Jewish identity. Skillfully drawing on Scholem's early diaries and writings, The Father of Jewish Mysticism introduces a young, soon-to-be legendary intellectual in search of himself and Judaism"--